(untitled) (Texas Journal of Medical Science, 2024)
Total protein, alkaline phosphatase, AST, ALT were determined by the Cypress Diagnostica (Belgium) test kit to evaluate the hepatoprotective activity in the serum of experimental toxic hepatitis model rats treated with polyphenol compounds. Blood was collected from animals, centrifuged at 3000 revolutions/min for 12 minutes, serum was separated and biochemical indicators studied